Class III OFPs function in the ER signaling pathway to regulate plant growth and development in Arabidopsis. Issue 1 (1st January 2019) - Wang, Xutong; Wang, Wei; Wang, Jie; Zhang, Na; Yang, Li; Cai, Ling; Hussain, Saddam; Chang, Ying; Wang, Shucai
ABSTRACT: Both OFPs and ERECTA (ER) regulate plant response to environmental stresses as well as plant growth and development. Blunt-endeded siliques, the characterized phenotype of the er mutants, was observed in transgenic plants overexpressing Class III OFP genes, including OFP13, OFP15, OFP16 and OFP18 . We found here that overexpression of ER restored the blunt-endeded siliques phenotypes observed in 35S:OFP15 or 35S:OFP16 plants, whereas er ofp15 and er ofp16 double mutants showed an overall phenotype similar to er single mutants, but their siliques were not blunt-endeded. By generating and characterizing transgenic plants overexpressing putative MAPK phosphorylation sites mutated OFP15 and OPF18, we found that phosphorylation status in Class III OFPs may affect their function in regulating plant growth and development. RT-PCR analysis showed that the expression levels of OFP15, OFP16 and OFP18 were increased in er mutants. Taken together, these results suggest that functions of Class III OFPs may depend on ER signaling.